IDENTIFICATION OF PUM KUTAJA AND STRI KUTAJA MENTIONED IN THE AYURVEDIC LITERATURE - Kumar Sanger, *Rupesh; Singh, D.C.; Chaubey, Suresh; Kumar, Naveen (International Journal of Ayurveda and Pharma Research, 2016)
Kutaja is one among the frequently used medicinal plants in Ayurveda. Kutaja is the drug of choice for bleeding piles. Acharya Charak quoted Kutaja tvak as the best Sangrahika dravya. It possess properties like Deepana and Pachana and is useful in the management of diarrhoea. Charak enumerated eighteen yogas of Kutaja with the name Vatsaka in Kalpasthana. In this context he described male and female varieties of Kutaja. Modern experts have also described two varieties of Kutaja i.e., Sveta and Krishna variety. The bark and seeds of Kutaja are used for different medicinal purposes. The seeds of Sveta Kutaja and the seeds which are Tikta, possess better medicinal property. The market sample comprises of seeds of both Tikta and Madhur variety mixed together. Market sample of Kutaja mostly comprises of Madhur seeds. There are three species taken under the name of Kutaja i.e., Holarrhena antidysentrica, Wrightia tomentosa and Wrightia tinctoria. It is a matter of confusion that which one is to be taken as Pum Kutaja and which one as Stri Kutaja. This article is to throw some light on different species taken as Kutaja and decide which species should be taken as Pum Kutaja and which one is to be taken as Stri kutaja.